Molecular Keys to the Janthinobacterium and Duganella spp. Interaction with the Plant Pathogen Fusarium graminearum - Haack, Frederike S.; Poehlein, Anja; Kröger, Cathrin; Voigt, Christian A.; Piepenbring, Meike; Bode, Helge B.; Daniel, Rolf; Schäfer, Wilhelm; Streit, Wolfgang R. (Frontiers in Microbiology, 2016)
Janthinobacterium and Duganella are well-known for their antifungal effects. Surprisingly, almost nothing is known on molecular aspects involved in the close bacterium-fungus interaction. To better understand this interaction, we established the genomes of eleven Janthinobacterium and Duganella isolates in combination with phylogenetic and functional analyses of all publicly available genomes. Thereby, we identified a core and pan genome of 1,058 and 23,628 genes. All strains encoded secondary metabolite gene clusters and chitinases, both possibly involved in fungal growth suppression. All but one strain carried a single gene cluster involved in the biosynthesis of alpha-hydroxyketone-like autoinducer molecules, designated JAI-1. Genome wide RNA-seq studies employing the background of two isolates and the corresponding JAI-1 deficient strains identified a set of 45 QS-regulated genes in both isolates. Most regulated genes are characterized by a conserved sequence motif within the promoter region. Among the most strongly regulated genes were secondary metabolite and type VI secretion system gene clusters. Most intriguing, co-incubation studies of J. sp. HH102 or its corresponding JAI-1 synthase deletion mutant with the plant pathogen Fusarium graminearum provided first evidence of a QS-dependent interaction with this pathogen.